ASEAN community: the legal challenges in achieving media diplomacy in the development of regional integration and empowerment - Saidatul Nadia Abd Aziz,; Salawati Mat Basir, (Penerbit Universiti Kebangsaan Malaysia, 2016)
In the era of integration, media plays a crucial role not only limited to conveying information and progress but also important to potray the image of an integration such as ASEAN COMMUNITY. While ASEAN is known for its diversity, media landscapes in ASEAN countries are also diverse and uneven. This had actually explained why it is extremely difficult to offer a general image of the regional media. In addition to that, this has been the main attribute hampering discussions and closer collaboration throughout these years in media-related activities, especially in setting common norms and standards of media practice. Although it was claimed under the charter, and the region's political-and-security and social-and-cultural blueprints, the need to promote the free flow of and access to information as well as the role of media in promotion of ASEAN identity and awareness in community-building and integration efforts, ASEAN leaders have yet to make serious efforts to push forward this platform. ASEAN community had always been ‘a work in progress’ and this is mainly due to the fact that ASEAN itself carries 10 different set of rules and laws thus making the road to achieve the integration of an ASEAN Community remains a big challenge. Therefore, this paper aims to provide an overview of the diversity of media landscape which includes the Freedom of Expression and the Right to Information in ASEAN member countries and the barriers in achieving media diplomacy for the sake of the development of regional integration.